Negative Regulators of Toll-like Receptor 4-Mediated Macrophage Inflammatory Response - Butchar, Jonathan P.; Parsa, Kishore V.L.; Marsh, Clay B.; Tridandapani, Susheela (Current Pharmaceutical Design, 2006)
Activation of macrophages through TLR4, the receptor for the bacterial endotoxin LPS, results in a potent inflammatory response aimed at eliminating the invading pathogen. Excessive production of inflammatory mediators is harmful to host tissue and in extreme cases can result in fatal outcomes. This inflammatory response is, therefore, tightly regulated by negative regulatory mechanisms that act to maintain homeostasis. This review will summarize recent advances in our current understanding of molecular mechanisms that regulate macrophage TLR4 signaling.
Keywords: PTEN